2012
DOI: 10.1007/s00894-011-1350-7
|View full text |Cite
|
Sign up to set email alerts
|

Anion recognition based on halogen bonding: a case study of macrocyclic imidazoliophane receptors

Abstract: The structures and properties of noncovalent interactions involving three imidazoliophane receptors 1-3 and halide anions have been investigated by means of density functional theory calculations. To account for the influence of the solvent environment, the implicit polarized continuum model was also employed. For the halogenated cyclophane receptors 1 and 2, the halide ions are held by a bidentate array of halogen bonds (C-Br/C-I...X(-)), while multiple hydrogen-bonding interactions (C-H...X(-)) are present i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 81 publications
(106 reference statements)
0
5
0
Order By: Relevance
“…The potential of C−X•••Y halogen bonding as a valuable tool to tune key interactions in crystal engineering processes and supramolecular self-assembly, is now well-recognized. 1,2 Therefore, and because of the awareness of its importance in various biochemical processes, 3 in molecular recognition, 4 and in drug design, 5,6 the phenomenon of halogen bonding has gained a tremendous increase in interest by theoreticians and experimentalists. 7 The majority of the papers dealing with C−X•••Y halogen bonding so far mainly concentrated on halogen donor molecules in which the carbon atoms involved are sp 3 hybridized.…”
Section: Introductionmentioning
confidence: 99%
“…The potential of C−X•••Y halogen bonding as a valuable tool to tune key interactions in crystal engineering processes and supramolecular self-assembly, is now well-recognized. 1,2 Therefore, and because of the awareness of its importance in various biochemical processes, 3 in molecular recognition, 4 and in drug design, 5,6 the phenomenon of halogen bonding has gained a tremendous increase in interest by theoreticians and experimentalists. 7 The majority of the papers dealing with C−X•••Y halogen bonding so far mainly concentrated on halogen donor molecules in which the carbon atoms involved are sp 3 hybridized.…”
Section: Introductionmentioning
confidence: 99%
“…8. The regression lines lead to a scale factor of 0.946(71) for the alkenes, 0.695 (9) for the alkynes and 0.568 (42) for the aromatic model compounds, respectively. These results tend to suggest that, for the interactions with alkenes, the predicted complexation enthalpies neatly reproduce the experimental values, with the differences between experiment and theory being in the order of a mere 5 to 10%.…”
Section: Relative Stabilitymentioning
confidence: 99%
“…Triggered by the growing number of applications in the field of crystal engineering [1,2] , supramolecular chemistry [3,4] and drug design [5,6] and by their role in several biochemical processes [7,8] and molecular recognition systems [9,10] , C-X … Y halogen bonds have recently gained large interest amongst experimentalists and theoreticians.…”
Section: Introductionmentioning
confidence: 99%
“…Anion complexation by synthetic host molecules is an important theme in supramolecular chemistry and is an area of intense interest that has relevance to biology, industry, and environment. In the past decade, experimental and theoretical studies have accumulated evidence for the existence of a variety of binding modes for complexes of anions with electron-deficient arenes. When the halide lies above the plane of the π system, the studies establish that three distinctly different types of interaction are possible: strong σ-type interactions, weak σ-type interactions, and anion−π interactions . Additionally, both experiment and theory reveal that electron-deficient arenes bearing C–H groups are potent hydrogen-bond donors, and aryl C–H···anion interactions are very common in supramolecular systems .…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, Berryman et al refined the nature of the first four interactions mentioned above (strong σ-type interactions, weak σ-type interactions, anion−π interactions, and HB) . The theoretical studies concerning XB between halogen-substituted arenes and anions have also been reported in recent years. However, to the best of our knowledge, a comprehensive and comparative study of all five interactions is still absent in the literature.…”
Section: Introductionmentioning
confidence: 99%